Ministry of Religious Affairs of Toba Samosir Regency Public Relations Performance to Increase Knowledge of Potential Pilgrims - Muhariman Siregar; Hasan Sazali; Indira Fatra Deni (IHSA Institute, 2022)
This study seeks to evaluate the public relations strategy of the Toba Samosir Regency Ministry of Religion in expanding the understanding of prospective Hajj pilgrims, as well as the inhibiting and supporting aspects of the Toba Samosir Regency Ministry of Religion's office in doing so. This study's data was collected through interviews, observations, and documentation, and then analyzed utilizing qualitative methodologies. The results of this study indicate that the Public Relations office of the Ministry of Religion of the Toba Samsir Regency employs the following strategies: 1) collecting data on prospective Hajj pilgrims in order to obtain facts; 2) educating the public about the importance of the Hajj; and 3) educating the public about the importance of the Hajj. 2) planning by compiling actions associated with the execution of the Hajj 3) Activity and communication, such as sociability, pilgrimage rites, and coaching 4) Evaluation, including performing in-depth reviews at both the district and provincial levels in conjunction with coordination meetings. The factors inhibiting public relations at the ministry of religion are differences in congregational characteristics, a lack of human resources at the ministry of religion office, and the distance between the ministry of religion office and the candidates' congregation, while the factors supporting public relations are the trust of prospective pilgrims in the committee, communication facilities, and the support of various parties.